2022
DOI: 10.1093/molbev/msac054
|View full text |Cite
|
Sign up to set email alerts
|

Looking through the Lens of the Ribosome Biogenesis Evolutionary History: Possible Implications for Archaeal Phylogeny and Eukaryogenesis

Abstract: Our understanding of microbial diversity and their evolutionary relationships has increased substantially over the last decade. Such an understanding has been greatly fuelled by culture-independent metagenomics analyses. However, the outcome of some of these studies and their biological and evolutionary implications, like the origin of the eukaryotic lineage from the recently discovered archaeal Asgard phylum, are debated. The sequences of the ribosomal constituents are amongst the most used phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 124 publications
(241 reference statements)
0
9
0
Order By: Relevance
“…A consideration for scenarios of viral karyogenesis is that current NCLDVs are generally engulfed by phagocytosing eukaryotes and are not known to infect archaea, which are often assumed to be ancestral to eukaryotes [ 117 , 120 , 121 ], though this latter hypothesis is disputed [ 105 , 122 125 ]. Indeed horizontal gene transfers from archaea to NCLDVs are extremely rare [ 77 ] and probably occur through amoebal “melting pots” [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A consideration for scenarios of viral karyogenesis is that current NCLDVs are generally engulfed by phagocytosing eukaryotes and are not known to infect archaea, which are often assumed to be ancestral to eukaryotes [ 117 , 120 , 121 ], though this latter hypothesis is disputed [ 105 , 122 125 ]. Indeed horizontal gene transfers from archaea to NCLDVs are extremely rare [ 77 ] and probably occur through amoebal “melting pots” [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors only proposed evolutionary scenarios in which Eukarya originated from a hypothetical Asgard with linked rRNA genes, based on the quantitative argument that "most existing phylogeny analyses placing the eukaryotic lineage within the Asgard archaea." Notably, Jüttner and Ferreira-Cerca also reported that unlinked rRNA genes are also frequent in DPANN and that "unlinked rRNA genes are more often found in symbiotic organisms" 65 . In my opinion, the existence of unlinked rRNA genes in practically all Asgard archaea is thus another argument supporting the idea that most of them are symbiotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, whereas Asgard viruses detected are typical for archaeal viruses, some authors emphasize the eukaryotic features of Asgard Caudoviricetes (head and tailed viruses), although these features are also present in some bacterial Caudovircetes 63 , 64 . Interestingly, Jüttner and Ferreira‐Cerca recently reported that all Asgard archaea, except Odinarchaea, have unlinked tRNA genes 65 . This strongly suggests that Asgard probably cannot be the ancestor of eukaryotes since, according to these authors, “ there is no known natural example of organisms with linked rRNA genes deriving from an ancestor with unlinked rRNA genes ,” and Eukarya were never grouped with Odinarchaea in 2D phylogenies.…”
Section: Discussionmentioning
confidence: 99%
“…How we will deal with this information will however be crucial to leverage the significance of these discoveries for our understanding of ribosome biogenesis. When reaching this point, emphasis toward functional similarity diversity of the ribosome biogenesis process, or its plasticity, will have to be carefully appreciated and will require to understand the genuine functional implication of these molecular features across different organisms' lifestyle and organisms' specific evolutionary history [169].…”
Section: Discussionmentioning
confidence: 99%